An exploratory study on impostor phenomenon among banking employees in New Zealand : a trait-state approach from a multi-generational perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, Albany, New Zealand. EMBARGOED until 12th March 2027 - Ge, Shanshan (Massey University, 2025)
The impostor phenomenon (IP) is a prevalent challenge that many individuals encounter at workplace, particularly in today’s rapidly evolving, uncertain, and multigenerational work environment driven by the technology revolution. However, little research has been conducted on the IP theoretical framework to apply these challenges and treat IP from both trait-state perspectives, rather than solely from a trait individualistic perspective. Unsurprisingly, a recent systematic review calls for more fine-grained research to better understanding of this phenomenon, its antecedents and consequences. Responding to this call, the researcher conducted a quantitative study in the competitive banking industry in New Zealand (NZ). Guided by self-determination theory (SDT), this study aims to explore the connection between generational identity (GI) and IP and the outcomes in terms of motivational behavioural intentions to which this connection may lead. The focus of this study is on the GI and IP constructs. The study further examines how different types of self-concept (i.e., self-doubt and internal locus of control) mediate the GI—IP relationship and how IP mediates the relationships between GI and motivational behavioural intentions (i.e. speak-up and promotion focus). In addition, this study examines how different leadership styles moderate the GI—IP relationship. The study recruited 285 employees from a major bank in NZ, including 55.79% females and 35.44% males. The majority identified as Caucasians and belonged to Generation X and Millennials. Over half of the participants had a Bachelor's degree or higher educational qualification and were in managerial positions. The study found no gender differences in scoring IP, while education level influenced IP. The study findings support the hypothesis that a negative relationship was found between generational identity and IP with a small size effect, with both types of self-concept being mediators. The generational cohort based on age was not related. While inclusive leadership moderated the relationship, transformational leadership did not. Additionally, a negative relationship was found between IP and the motivational behavioural intentions, speak-up, but not with the intention of promotion focus. This study’s findings showed the important effects of individual traits on IP in the current banking climate with ongoing transformational changes driven by technology disruption, and that effective leadership can support banking employees by fostering an inclusive environment where individuals can thrive. The study also opens a new dialogue about how generational identity (GI) could foster a sense of belonging, which is very important at times of uncertainty and change due to technological advancement in the multi-generational workplace.
Embargoed until 12th March 2027
Keywords: 520104 Industrial and organisational psychology (incl. human factors)